Analisis Afinitas Sastra (Perbandingan Puisi “Mahallul Qiyam” Simtudduror dan Barzanji): Kajian Sastra Bandingan - Saukani, Muhammad; Hakim, Lukmanul (Institut Agama Islam Negeri Metro, 2024)
Literature is a person's imagination that produces a creation or work through beautiful language and is able to bring people who read it into the work because the language is so stunning. Literature can be used for things we like, we like, such as literature written by one of the Hadramaut scholars, Yemen, namely Al-Habib Ali bin Muhammad Al-Habsyi. He composed a beautiful poem called the Maulid book in the Mahallul Qiyam section. Shaikh Ali bin Muhammad Al-Habsyi wrote this poem because of his love for the Prophet Muhammad SAW. Likewise, a scholar named Ja'far bin Hasan bin Abdul Karim bin Sayyid Muhammad Al-Madani, he also wrote a poem or Mahallul Qiyam which is contained in his Maulid book. They both wrote works with the same aim, namely praising Rasulullah SAW because of their love for His Majesty Rasulullah SAW. However, the problem found by researchers here is that there are similarities between these two works, especially in the Mahalul Qiyam section even though the authors are different. The similarities can be seen from the narratives used, the metaphors are different but have similarities in every row of words in the verse. So from this problem the researcher aims to study these two texts limited to the Mahalul Qiyam part, the researcher uses comparative literary studies. Researchers look for points of similarity and difference that reveal the relationship that exists between one work and another, and look for similarities, differences and influences between the two pieces of literature being compared. The research method used is a qualitative descriptive method, which is research about research that is descriptive in nature and tends to use analysis. The research results found revealed differences and similarities in the texts of the two Mahalul Qiyam Simtuddurar and Barzanji in terms of thematic affinity, literary style, emotionality, and history or narrative.